Analisis Bibliometrik Tentang Arkeologi Islam - M Kafi Maulana; Imam Yuadi (Jurnal Tamaddun, 2022)
Islamic archeology is a science that studies elements of Islamic culture related to ancient objects, either containing part or all of these objects which contain elements of Islam as a form of the depiction of Muslims in the past. Taken from the Scopus published database from 2011 to 2020. One of the keywords used, Islamic archeology to achieve results in accordance with bibliometric research to be carried out. The bibliometric data were analyzed and visualized using VosViewer. keyword results as many as 9110 in the data obtained, 90 stated in accordance with the requirements for the emergence of keywords in keywords. and there are 2821 links or number of relationships in the visualized data. In addition, biblioshiny analysis was carried out by visualizing the word cloud of themes or subjects that were connected to the subject of Islamic archaeologists.